Contribution of carbon nanotubes to vibration damping behavior of epoxy and its carbon fiber composites. (April 2020) - Avil, Esma; Kadioglu, Ferhat; Kaynak, Cevdet
The main objective of this study was to investigate contribution of the non-functionalized multi-walled carbon nanotubes on the vibration damping behavior of first neat epoxy resin and then unidirectional and bidirectional continuous carbon fiber reinforced epoxy matrix composites. Epoxy/carbon nanotubes nanocomposites were produced by ultrasonic solution mixing method, while the continuous carbon fiber reinforced composite laminates were obtained via resin-infusion technique. Vibration analysis data of the specimens were evaluated by half-power bandwidth method; and the mechanical properties of the specimens were determined with three-point bending flexural tests, including morphological analyses under scanning electron microscopy. It was generally concluded that when even only 0.1 wt% carbon nanotubes were incorporated into neat epoxy resin, they have contributed not only to the mechanical properties (flexural strength and modulus), but also to the vibration behavior (damping ratio) of the epoxy. When 0.1 or 0.5 wt% carbon nanotubes were incorporated into continuous carbon fiber reinforced epoxy matrix composites, although they have no additional contribution to the mechanical properties, their contribution in terms of damping ratio of the composites were significant.